2018
DOI: 10.1016/j.ijid.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical features and early warning indicators of death from severe fever with thrombocytopenia syndrome

Abstract: Neurological signs, hemorrhagic manifestations, disturbance of consciousness, hyponatremia, prolonged APTT, and increased CRP and serum creatinine are risk factors for death in SFTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
6
28
1
Order By: Relevance
“…Other viral infections associated with hyponatremia include human herpesvirus-6 (HHV-6), SFTS virus (SFTSV), hantavirus, herpes simplex virus (HSV), and Ebola virus infections [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Hyponatremia Due To Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other viral infections associated with hyponatremia include human herpesvirus-6 (HHV-6), SFTS virus (SFTSV), hantavirus, herpes simplex virus (HSV), and Ebola virus infections [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Hyponatremia Due To Infectionsmentioning
confidence: 99%
“…Severe fever with thrombocytopenia syndrome (SFTS) is an infectious disease caused by the SFTSV. Retrospectively, SFTSV infections are uncommon but are associated with high mortality, reported at the level of 33% [ 34 ]. Hyponatremia was found to be an independent risk factor of death in SFTS patients.…”
Section: Hyponatremia Due To Infectionsmentioning
confidence: 99%
“…Preexisting chronic comorbidity is also an attribute that should be considered, since a large part of SFTS patients were the elderly and frequently afflicted by various underlying conditions which conferred an increased risk of adverse outcomes following infection. Previous studies revealed that adverse outcomes of SFTS patients were associated with comorbidities (Deng et al, 2013;Xu et al, 2018;Zhang et al, 2019), which were specifically identified to be diabetes mellitus (DM), chronic virus hepatitis (CVH), and 1 https://is.kdca.go.kr 2 https://www.niid.go.jp chronic obstructive pulmonary diseases (COPD) in one study (Zhang et al, 2019). Up to now, no studies in analyzing the risk of SFTS mortality have ever tried to disentangle the effect from age, sex, or comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system disorders, multiple organ failure, elevated serum AST/ALT/LDH/CK levels, high viral loads, and hemorrhagic symptoms have been reported as factors associated with fatal SFTS . Previous reports have described gastrointestinal, pulmonary, and gingival hemorrhages and subcutaneous petechiae but not intracranial hemorrhage . Only 3 cases of SFTS with intracranial hemorrhage have been identified, all of which were fatal.…”
Section: Discussionmentioning
confidence: 99%